Comparative study of the atmospheric chemical composition of three South American cities - Vasconcellos, Pérola C. (2011)
PM10 samples were collected in 2008 at three sites in South America in the framework of an international project (South American Emissions Megacities, and Climate; SAEMC). The concentration of metals, metalloids, ion and organic compounds of most PM10 samples collected at three sites (Buenos Aires (BAI), Bogotá (BOG) and São Paulo (SPA)) is below the air quality standard of the respective countries. At the sites n-alkanes and carbon preference index distribution indicated the influence of petroleum residues derived from vehicular emissions. Most PAH detected are attributed to light-duty gasoline vehicles and to stationary sources. At all sites benzo[a]pyrene equivalent values mean a significant cancer risk. Sulfate, nitrate, ammonium, calcium and sodium are the most abundant water-soluble ions at the three sites. Ammonium sulfate is likely the form presented for these species formed by photochemical reactions of precursors emitted mainly by vehicles. At BAI and SPA, formate/acetate ratios indicated the contribution of photochemical reactions; on the contrary, at BOG site, acetate is predominant, indicating strong contribution of vehicular emissions. São Paulo samples showed the highest concentrations of elements among all the sites. None of the toxic or potentially toxic elements exceed the guideline values of the World Health Organization. At BAI site earth crust seems to be the major source of Fe and Mn; at SPA, anthropogenic source is responsible for Pb and Zn presences. Traffic related element is well correlated at the three sites.